Tối ưu hóa quá trình trích ly dầu mù u bằng kỹ thuật lưu chất siêu tới hạn - Hiếu, Nguyễn Hữu; Huy, Nguyễn Trọng; Minh Thùy, Trần Thị (Vietnam Journal of Chemistry, 2016)
In this research, tamanu oil was extracted from seeds using supercritical fluid CO2 (SCF-CO2). Rotatable experimental design method (Box and Hunter) was applied to optimize the operating conditions of the SCF-CO2 technique as pressure, flow rate, and time. Optimization results show that the highest oil yield was obtained of 37.28% at 280 bar, 18 g CO2/min, and 180 minutes. This oil yield extracted by the SCF-CO2 method was 1.4 times higher than that of conventional Soxhlet extraction using petroleum ether. The analysis results of gas chromatography–mass spectrometry (GC-MS) and physicochemical properties (oxidation value, iodine value) indicate that the quality of tamanu oil extracted with SCF-CO2 was better than that of products obtained by organic solvent and cold-pressed extraction methods. Keywords. Optimization, extraction, supercritical CO2, tamanu oil